REPRODUÇÃO INDUZIDA DE PIAU CORRÓ (Leporinus lacustris), COM DIFERENTES INDUTORES HORMONAIS - TAVARES, Tainara Vieira; ACUNHA, Rubia Mara Gomes3 (rubia.zootec18@gmail.com; SANTOS, Jussara Garrido; WANDERLEY, Alysson Martins; COSTA, Deliane Cristina; AMARAL, Cristiane Meldau de Campos (ANAIS DO ENIC, 2023)
-